A Comprehensive Review of Magnetic Nanomaterials Modern Day Theranostics - Gul, Saima; Khan, Sher Bahadar; Rehman, Inayat Ur; Khan, Murad Ali; Khan, M. I. (Frontiers in Materials, 2019)
Substances at nanoscale commonly known as “nanomaterials” have always grabbed the attention of the researchers for hundreds of years. Among these different types of nanomaterials, magnetic nanomaterials have been the focus of overwhelming attention during the last two decades as evidenced by an extraordinary increase in number of research papers. Iron oxide magnetic nanoparticles have occupied a vital position in imaging phenomena; as drug vehicles, controlled/sustained release phenomena and hyperthermia; atherosclerosis diagnosis; prostate cancer. In fact, these are wonderful “theranostic” agents with some are under clinical trials for human use. In this review, we have attempted to highlight the advances taking place in the field of magnetic nanoparticles as theranostic agents. Extensive progress has been made in the two most important parameters viz. control over size and shape which decide the importance of iron oxide magnetic nanoparticles by developing suitable procedures like precipitation, co-precipitation, thermal decomposition, hydrothermal synthesis, microemulsion synthesis and plant mediated synthesis. After suitable synthetic route, workers encounter the most daunting task linked with the materials at nanoscale i.e. the protection against corrosion. Only properly protected iron oxide magnetic nanoparticles can be further connected to different functional systems to make building blocks for application in catalysis, biology and medicines. Finally, iron oxide magnetic nanoparticles play a key role in imaging applications for diagnostic purposes, drug delivery vehicles and above all the combined effect of previous two phenomena “theranostics”. With all the potential uses, toxicity of the of iron oxide magnetic nanoparticles has also been discussed. In the end, attention has been drawn to address the future of research trends of iron oxide magnetic nanoparticles in theranostics.